2023
DOI: 10.1007/s00216-023-04721-8
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the boundaries of atomic spectroscopy at the single-cell level: critical review of SP-ICP-MS, LIBS and LA-ICP-MS advances for the elemental analysis of tissues and single cells

Abstract: Metals have a fundamental role in microbiology, and accurate methods are needed for their identification and quantification. The inability to assess cellular heterogeneity is considered an impediment to the successful treatment of different diseases. Unlike bulk approaches, single-cell analysis allows elemental heterogeneity across genetically identical populations to be related to specific biological events and to the effectiveness of drugs. Single particle-inductively coupled plasma-mass spectrometry (SP-ICP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 155 publications
0
5
0
Order By: Relevance
“…While Wang et al [ 30 ] recently showed that the heterogeneity of elements within tumor cells can be used for LIBS-based discrimination of different tumor cell lines, our study proves that the distribution of elements is also significantly different between different areas within mandibular bone-infiltrating head and neck tumors. Further development of nano-LIBS systems is expected to have great potential for cellular research in the future [ 31 ], which could also contribute to addressing current challenges in the diagnosis and treatment of head and neck cancers.…”
Section: Discussionmentioning
confidence: 99%
“…While Wang et al [ 30 ] recently showed that the heterogeneity of elements within tumor cells can be used for LIBS-based discrimination of different tumor cell lines, our study proves that the distribution of elements is also significantly different between different areas within mandibular bone-infiltrating head and neck tumors. Further development of nano-LIBS systems is expected to have great potential for cellular research in the future [ 31 ], which could also contribute to addressing current challenges in the diagnosis and treatment of head and neck cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Two review papers cover the use of atomic spectrometry techniques for imaging of biological samples (Section 6.2). Davison et al 19 discussed the state-of-the-art and perspectives of single cell analysis using spICP-MS, LIBS and LA-ICP-MS, whereas the work of Peng et al 20 was devoted to explore the use of multiple laser imaging techniques and nanomaterials to improve cancer diagnosis in vivo .…”
Section: Reviewsmentioning
confidence: 99%
“…1 Additionally, two review papers have covered the use of spectroscopy-based imaging for biological research . Davison et al 19 provided an evaluation of single cell analysis utilising spICP-MS, LIBS and LA-ICP-MS. The advantages and limitations were assessed, concluding that more than one technique was required to fully elucidate processes and that calibration and standardisation still require further development.…”
Section: Applications: Clinical and Biological Materialsmentioning
confidence: 99%
“…LA-ICP-MS can perform in situ analyses rapidly and in real-time on a micro-scale. It offers several advantages, including easy sample preparation, minimal contamination levels, high spatial resolution, sensitivity, low detection limits, provides relatively simple spectra while allowing for simultaneous determination of multiple elements and information about isotope ratio ( Trejos and Almirall, 2005 ; López-Fernández et al., 2016 ; Nunes et al., 2016 ; Davison et al., 2023 ; Janovszky et al., 2023 ).…”
Section: Detection and Analysis Techniques Of Hms In Plantsmentioning
confidence: 99%